Patient safety associated with the surgical treatment of bone and soft tissue tumours during the COVID-19 pandemic—results from an observational study at the Oxford Sarcoma Service - Rajasekaran, RB; Kotecha, S; Whitwell, D; Cosker, TDA; Critchley, P; Fries, CA; Pigott, D; Gibbons, CLMH; Carr, A (Springer, 2020)
Purpose Deferring cancer surgery can have profound adverse effects including patient mortality. During the COVID-19 pandemic, departmental reorganisation and adherence to evolving guidelines enabled provision of uninterrupted surgical care to patients with bone and soft tissue tumours (BST) in need of surgery. We reviewed the outcomes of surgeries on BST during the first two months of the pandemic at one of the tertiary BST centres in the UK.